Post-discharge surveillance of wound infections by telephone calls method in a Sudanese Teaching Hospital - Abubaker Ibrahim Elbur; Yousif MA; Ahmed S.A. ElSayed; Manar E. Abdel-Rahman (Elsevier, 2013)
Summary: Surveillance of wound infections has been shown to be a powerful preventive tool, and feedback to the clinical staff reduces wound infection rates. The main objectives of this study were to identify the applicability of telephone calls as a method of post-discharge wound infection surveillance, and to identify patients and procedures characteristics associated with loss for follow-up after hospital discharge. Materials and methods: This was a prospective cohort study conducted in Khartoum Teaching Hospital, Sudan. Patients, aged >18 years admitted for elective clean and clean-contaminated surgery during March 1st to 31st October 2010 were recruited. 1-month surveillance of wound infections was conducted with telephone interviews. Results: Overall 3656 patients were operated on. Of them 1769 (48.4%) were eligible {mean age 37.8 + 14 years; females, n = 1472 (83.3%)}. The performed surgical interventions were 1814. Of these 1277 (70.4%) were clean-contaminated and 537 (29.6%) were clean. Patients who successfully completed the follow-up were 1387 (78.4%), while 368 (20.8%) were lost, and 14 (0.8%) died. The percentage of male patients (85.3%) who successfully completed the follow-up was significantly higher than females (77.8%); (P = 0.002). Wound infection was detected in 15 (0.8%) cases during hospital stay and 110 (6.2%) others after hospital discharge. Conclusions: The majority of wound infections in the current study appeared in post-discharge period; this emphasis the need for establishment of surveillance program in the hospital. Surveillance of wound infections using telephone calls is applicable in this setting and can be used as an alternative method to clinic-based diagnosis of wound infections. Keywords: Surveillance, Wound infections, Telephone calls, Sudan